Growth response of Catlacatla (Hamilton,1822) raised in manured tanks on low fishmeal diets,with a note on carcass composition and digestive enzyme activity - Manjappa, K.; Keshavanath, P.; Gangadhar, B. (Indian Journal of Fisheries, 2016)
Low fishmeal diets (10%) with varied levels of maize (40-31%) and sardine oil (0-9%) were fed for 120 days to triplicate groups of catla (Catla catla Hamilton,1822) fingerlings (average weight 1.84-1.90 g) stocked @ 1 fish per m2 in cement tanks with soil base fertilised with poultry manure. Fish fed on diet containing 6% oil and 34% maize (T2) showed the highest (p0.05) in enzyme activity was observed in the hepatopancreas of the control and treated fish. The results indicated beneficial effects of incorporating maize and fish oil in low fishmeal diet for catla.